YOGA ATASI NYERI SAAT MENSTRUASI PADA REMAJA PUTRI - Julaecha Julaecha (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Menstruation is part of a regular process that prepares a woman's body every month for pregnancy, which is controlled by the interaction of hormones released by the hypothalamus. In general, women experience physical discomfort for several days before and during the first day of menstruation in the form of pain or dysmenorrhea. Dysminorrhea is pain that arises during menstruation which can interfere with daily activities. The prevalence of dysminorrhea in Indonesia around 50% occurs in young women. As a result of menstrual pain, among others: about 20% of adolescents can not go to school because of pain during menstruation, so that academic achievement decreases. There are several pain management to overcome dysminore one of which is with yoga. The purpose of community service is to provide information to adolescents about how to cope with pain during menstruation without painkillers with yoga movements the balasana movemens. The materials used in this activity were leaflets, infocations, laptops, questionnaires and stationery, while this activity was carried out on April 13-15 at MTS Darussalam Al-Hafiz Jambi City. The results of this community service were female students knowing how to overcome pain during menstruation by doing one of the yoga poses of child pose to reduce pain during menstruation.